2005
DOI: 10.1214/009117905000000396
|View full text |Cite
|
Sign up to set email alerts
|

Edge-reinforced random walk on a ladder

Abstract: We prove that the edge-reinforced random walk on the ladder ${\mathbb{Z}\times\{1,2\}}$ with initial weights $a>3/4$ is recurrent. The proof uses a known representation of the edge-reinforced random walk on a finite piece of the ladder as a random walk in a random environment. This environment is given by a marginal of a multicomponent Gibbsian process. A transfer operator technique and entropy estimates from statistical mechanics are used to analyze this Gibbsian process. Furthermore, we prove spatially expon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 15 publications
3
62
0
Order By: Relevance
“…This description was first given by Coppersmith and Diaconis in [CD86] and refined by Keane and Rolles in [KR00]. It has already been useful to analyze edge-reinforced random walk on certain infinite graphs, including ladders of arbitrary width, by taking the infinite volume limit of finite subgraphs; see [MR05b], [Rol05], and [MR05a]. However, in this paper, we do not make use of the explicit form of the mixing measure for finite graphs.…”
Section: Introductionmentioning
confidence: 99%
“…This description was first given by Coppersmith and Diaconis in [CD86] and refined by Keane and Rolles in [KR00]. It has already been useful to analyze edge-reinforced random walk on certain infinite graphs, including ladders of arbitrary width, by taking the infinite volume limit of finite subgraphs; see [MR05b], [Rol05], and [MR05a]. However, in this paper, we do not make use of the explicit form of the mixing measure for finite graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, recurrence results were obtained. The following result was proved in [22]. The result was extended in [29], under the assumption the initial weight a is large: Theorem 7.2.…”
Section: Reinforced Random Walk On Laddersmentioning
confidence: 97%
“…The later development indeed followed this idea: In [5], it was shown that the edge-reinforced random walk on the ladder Z × {1, 2} with all initial weights equal to the same constant b > 3/4 is recurrent. For the edge-reinforced random walk on Z×T with a finite tree T and constant large initial weights, recurrence was shown in [11].…”
Section: Introductionmentioning
confidence: 93%
“…The techniques used below are different from the methods in [5,7,11]. To analyze the edge-reinforced random walk on the infinite periodic graph, we first study the process on finite periodic graphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation